Penerapan Algoritma Kompresi Pada Sistem Pengaduan Layanan Masyarakat Online - I Gusti Agung Gede Arya Kadyanan (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2019)
Handling complaints is a reciprocal service for the public provided by the government. People who want to make a complaint can make it by dialing the phone number, web, emails and suggestion box provided by the government. Problems encountered in making this complaint include an error in entering/writing the targeted agency, the distance to the suggestion box is far and not real time. The author designed a mobile-based information system for handling public complaints using the android operating system. This public complaint handling application has a feature where the user can choose the agency in accordance with the complaint, the complaint can include pictures, location tags, can see the lates developments of complaint handling in the status of complaints, as well as chat feature that can be used to communicate directly with the Government and the Admin Agencies. Based on the result of test conducted, namely testing using black box method and stress testing, it can be concluded that this application has functioned properly. Keywords: Image, Boxblur Algorithm, Information System, Compression